Smart-Flow: An IoT-Enabled Automated Petrol Pump System - Mr. Jivan Rajendra Jadhav,; Mr. Atharva R. Kumbhar,; Mr. G.B. Koravi,; Mrs. Swapnali V. Jagtap, (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Traditional fuel dispensing systems rely heavily on manual operations, which often result in inaccurate fuel measurement, long waiting times, lack of transparency, and operational inefficiencies. With the rapid growth of smart infrastructure and digital payment adoption, there is a strong need for an automated and reliable fuel dispensing solution. This paper presents Smart-Flow, an IoT-enabled automated fuel dispensing system that integrates precise flow sensing, microcontroller-based control, and hybrid payment mechanisms supporting both cash and UPI-based transactions. The system ensures accurate fuel delivery, reduces human intervention, and enables real-time data monitoring through cloud connectivity. Experimental observations indicate improved dispensing accuracy, faster service time, and enhanced transparency compared to traditional fuel stations. The proposed system is suitable for modern fuel stations and smart city applications.
Keywords: Automated Fuel Dispensing; Flow Sensor; Hybrid Payment System; IoT; Smart Infrastructure; UPI Integration